Construction project in Kuwait international airport cargo city: issue of conflict management - Mohammed Kh Th E, Aalazemi; Mohiuddin, A. K. M. (Deer Hill Publications, 2019)
Conflict in construction projects seems to be the reasons of high project cost, project delays, lower productivity, loss of profit, damage business relationships and dispute on the team. Effective functioning requires commitment of at least several key personnel to get the venture runs effectively even with the presence of distinctive intrigue. When individuals of fluctuating foundation meet-up on a task group, strife is unquestionably present there. As the individuals inside the venture alliance are interrelated, intrigue impacts and clashes are not uncommon within their activities. This study therefore sought to discover the causes of these conflicts in the construction sector and the manner by which these conflicts can be effectively resolved. Here a quantitative survey-type study has been carried out on construction project in Kuwait international airport for conflict management. One hundred eighty eight questionnaires have been distributed, fourteen of them have been lost and eleven of them have not been answered. The responses of 163 participants have been analyzed with the Statistical Package for Social Scientists (SPSS). This study showed that the general causes of conflict are predominantly create conflicts. Inadequate communication and contradicting instructions according to the results are the leading causes of conflict. The effects of conflict on project mainly include project delays, ineffective construction and reduced productivity, etc. The findings revealed that participants in the study prefer the role of collaborating and compromising styles in solving conflict of on-site construction. Every project starts and ends with communication, so communication is the life wire of all construction projects. To cure the communication problem, the study suggests strategies like Team Meeting Discussions, Site Review Meetings, and Project Status Reporting platform to manage the conflict and reduce the dispute of construction projects.